G-CSF (filgrastim) treatment for amyotrophic lateral sclerosis: protocol for a phase II randomised, double-blind, placebo-controlled, parallel group, multicentre clinical study (STEMALS-II trial) - Christian Lunetta; Letizia Mazzini; Jessica Mandrioli; Isabella Laura Simone; Giuseppe Marrali; Claudia Caponnetto; Vincenzo La Bella; Corrado Tarella; A Bombaci; M Brunetti; S Cammarosano; A Canosa; et al. (BMJ Open)
Introduction Amyotrophic lateral sclerosis (ALS) is a fatal progressive neurological disorder characterised by a selective degeneration of motor neurons (MNs). Stem cell transplantation is considered as a promising strategy in neurological disorders therapy and the possibility of inducing bone marrow cells (BMCs) to circulate in the peripheral blood is suggested to investigate stem cells migration in degenerated ALS nerve tissues where potentially repair MN damage. Granulocyte-colony stimulating factor (G-CSF) is a growth factor which stimulates haematopoietic progenitor cells, mobilises BMCs into injured brain and it is itself a neurotrophic factor for MN. G-CSF safety in humans has been demonstrated and many observations suggest that it may affect neural cells. Therefore, we decided to use G-CSF to mobilise BMCs into the peripheral circulation in patients with ALS, planning a clinical trial to evaluate the effect of G-CSF administration in ALS patients compared with placebo.Methods and analysis STEMALS-II is a phase II multicentre, randomised double-blind, placebo-controlled, parallel group clinical trial on G-CSF (filgrastim) and mannitol in ALS patients. Specifically, we investigate safety, tolerability and efficacy of four repeated courses of intravenous G-CSF and mannitol administered in 76 ALS patients in comparison with placebo (indistinguishable glucose solution 5%). We determine increase of G-CSF levels in serum and cerebrospinal fluid as CD34+ cells and leucocyte count after treatment; reduction in ALS Functional Rating Scale-Revised Score, forced vital capacity, Scale for Testing Muscle Strength Score and quality of life; the adverse events/reactions during the treatment; changes in neuroinflammation biomarkers before and after treatment.Ethics and dissemination The study protocol was approved by the Ethics Committee of Azienda Ospedaliera Universitaria ‘Città della Salute e della Scienza’, Torino, Italy. Results will be presented during scientific symposia or published in scientific journals.Trial registration number Eudract 2014-002228-28.